LGBT Perspektif Hukum Islam dan UU HAM Nomor 39 Tahun 1999 - Tamba, Sulaiman (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
Marriage in LGBT against nature has been against the nature of human life that strives to establish inner and biological bonds between the opposite sex, namely between men and women. A positive legal review emphasizes the Marriage Law stating that marriage is built on the basis of the marriage law that regulates marriage as an inner bond between men and women for women, households and families, and helps to uphold religion and use customs. In addition, the human rights perspective also provides guarantees for families related to marriage institutions through their harmless relationships in social life such as transmitting sexually transmitted diseases. While discussing Islamic law clearly and severely linking similar marriages are classified as haram, this is considered to be no longer in accordance with the syar 'argument, this is related to texts in the Qur'an and Hadith as the basis of Islamic law. Therefore, efforts should be made to oppose LGBT relations in order to avoid ignorance and even challenge challenges. One effort that can be done is to criticize and actualize religious interpretations (interpreting the story of Lut and the concept of marriage) which does not favor the LGBT people.